2021
DOI: 10.15561/20755279.2021.0508
|View full text |Cite
|
Sign up to set email alerts
|

Beach volleyball athlete training trends of Russian-language scientific resources: a systematic review

Abstract: Background and Study Aim. The inclusion of beach volleyball in the program of the Olympic Games gave some impetus to the development of scientific research on various problems of training athletes. Most of the research results are presented in journals included in the Web of Science Core Collection. However, the publication of research results in journals from national databases remains outside the scope of this database. The aim of this study is to systematically review the scientific literature on various be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…There have been numerous theoretical and empirical studies on the current state of physical fitness training research, difficulties that exist, and potential directions for growth by domestic scholars in recent years. Studies on physical training theory and practice in the United States and overseas tend to focus on the microcosmic level of understanding and quantitative analysis, instead of the macrocosmic level [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous theoretical and empirical studies on the current state of physical fitness training research, difficulties that exist, and potential directions for growth by domestic scholars in recent years. Studies on physical training theory and practice in the United States and overseas tend to focus on the microcosmic level of understanding and quantitative analysis, instead of the macrocosmic level [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This article selects four main items in the McGill test: lumbar flexion, extension, right bridge, and left bridge. 4 This paper examines athletes' core strength test results before and after the test.…”
Section: Test Schemementioning
confidence: 99%
“…Although the presentation of bibliometric analysis research through visualised maps has been quite widespread in recent years, it is observed that such research is limited to certain areas. In this regard, some bibliometric studies in the field of physical education and sports were detected by scanning the "Web of Science (WoS)" database Contreras-Barraza et al, 2021;Chiu et al, 2021;Iermakov et al, 2021;Baier-Fuentes et al, 2020;Tomanek & Lis, 2020;Jiménez-García et al, 2020;Büyükbaykal & İli, 2020;Gholampour et al, 2019;Huertas González-Serrano et al, 2020;Lis, 2020;Chamberlain, 2019). Even though the visibility of systematic compilation studies has been increasing in the physical education and sports literature in recent years as mentioned above, the number of bibliometric studies seems rather limited.…”
Section: The Aim and Significance Of The Studymentioning
confidence: 99%